2011
DOI: 10.1111/j.1540-5907.2010.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Winning Coalition Formation in the U.S. Senate: The Effects of Legislative Decision Rules and Agenda Change

Abstract: Recent empirical work has brought a renewed attention to the effect congressional rules of procedure have on the size of winning coalitions. Specifically, scholars have posited that legislative success hinges on the support of legislators identified by institutionally defined decision rules. Under these theories, supermajority decision rules in the U.S. Senate lead to larger, more inclusive coalitions on final passage. In this article, I reevaluate these claims by controlling for changes in the legislative age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Senate Rule 11 in 1820 specified, When a question is under debate, no motion shall be received but to adjourn, to lie on the table, to postpone indefinitely, to postpone to a day certain, to commit, or to amend; which several motions shall have precedence in the order they stand arranged, and the motion for adjournment shall always be in order, and be decided without debate. ( (Lynch & Madonna, 2013;Madonna, 2011), we remain confident that the universe of all tabling motions is not much greater than the number that appeared with a recorded vote. This is due to a combination of factors.…”
Section: Discussionmentioning
confidence: 93%
“…Senate Rule 11 in 1820 specified, When a question is under debate, no motion shall be received but to adjourn, to lie on the table, to postpone indefinitely, to postpone to a day certain, to commit, or to amend; which several motions shall have precedence in the order they stand arranged, and the motion for adjournment shall always be in order, and be decided without debate. ( (Lynch & Madonna, 2013;Madonna, 2011), we remain confident that the universe of all tabling motions is not much greater than the number that appeared with a recorded vote. This is due to a combination of factors.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple points of disconnect can occur as one moves from theorising (and hypothesis generation) to testing; that is, in constructing an empirical research design, a number of important decisions have to be made about data, the construction of measures and model specification 41 . To focus only on one of these decisions here, as Howell et al (2000), Madonna (2011), Jenkins and Monroe (2016) and others have shown, how variables are constructed – whether it be the dependent variable or the key independent variable(s) – can have a significant impact on the results recovered, and whether expectations are met. The empirical literature on Pivotal Politics, we believe, should also serve as a cautionary tale in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the behaviors of the senators we chose to use their roll-call votes [36], a popular choice for determining similarities, differences, and coalitions between political members [14,16,17,20]. We initially investigated the structure of the current Senate in the 116th Congress.…”
Section: Methodsmentioning
confidence: 99%